Exhibiting apartheid: whites, Malays, and absent slaves in the displays of the South African Cultural History Museum - Mazel, Aron (Southern African Humanities, 2019)
On 6 April 1966, there was a whites-only display opening for the newly established South African Cultural History Museum in Cape Town. A week later, on 13 April, there was a separate opening for the Malay community. This paper chronicles the attitudes and circumstances leading to the creation of the displays and the ideological imperatives that informed them. It demonstrates that Malays and slaves were both included in the first display schedule, developed in 1959, although the emphasis was on European culture, white nation-building, and ‘ancient civilisations’. Yet when the museum opened in 1966, slavery was omitted, despite the fact that it was housed in the Slave Lodge, while the Malays were given an expanded format, without reference to slavery, even though many had been brought to the Cape as slaves. The reasons for this outcome are explored, proposing that apartheid ideologues were continuing a trend in their understanding of Cape history that denied slave history for decades in order to avoid uncomfortable questions being asked about the labour that had been used to build the Cape colony. In contrast, the Malays were included to emphasise their perceived link to the Afrikaners, such as their role in the development of Afrikaans. KEY WORDS: Apartheid, ‘civilisation’, displays, ideology, slavery, Malays, South African Cultural History Museum.